2021
DOI: 10.1002/bit.27991
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal titration calorimetric assessment of lignin conversion by laccases

Abstract: Lignin valorization may offer a sustainable approach to achieve a chemical industry that is not completely dependent on fossil resources for the production of aromatics.However, lignin is a recalcitrant, heterogeneous, and complex polymeric compound for which only very few catalysts can act in a predictable and reproducible manner.Laccase is one of those catalysts and has often been referred to as an ideal "green" catalyst, as it is able to oxidize various linkages within lignin to release aromatic products, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The calorimetric assessment of lignin oxidation by different bacterial and fungal laccases was performed using the IrCal method (Figure 1) (A. Islam et al, 2022). This showed that the extent of lignin conversion, as measured from the apparent molar enthalpy, and the rate of that conversion, obtained from the power, showed large differences among the different enzymes.…”
Section: Initial Rate Calorimetry Using the Ircal Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The calorimetric assessment of lignin oxidation by different bacterial and fungal laccases was performed using the IrCal method (Figure 1) (A. Islam et al, 2022). This showed that the extent of lignin conversion, as measured from the apparent molar enthalpy, and the rate of that conversion, obtained from the power, showed large differences among the different enzymes.…”
Section: Initial Rate Calorimetry Using the Ircal Methodsmentioning
confidence: 99%
“…Here ITC can offer a pragmatic solution by measuring the overall conversion of lignin by an enzyme. This has been done for the lignin conversion by different laccase variants and showed that the extent of conversion and the rate of that conversion can be determined (Figure 1), although the precise molecular nature of the products needs to be determined independently (Islam et al, 2022).…”
Section: Difficult Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Solution-based spectrophotometric assays are unsuitable for measuring the oxidative rates of non-soluble lignin by laccase (Valles et al 2020 ). Recently, advanced techniques such as 2D NMR, nanostructure-initiator mass spectrometry (NIMS), electron paramagnetic resonance (EPR) spectroscopy, and isothermal titration calorimetric (ITC) have been developed to study lignin depolymerization by laccase (Deng et al 2018 ; Perna et al 2019 ; ST et al 2022 ). These methods present distinct advantages over solution-based spectrophotometric assays: NIMS offers abundant information on bond cleavage and quantitative analysis of product generation along with kinetics, EPR enables monitoring the kinetics of radical formation during the laccase-catalyzed conversion of lignin, and ITC can gain independent information on the extent and rate of lignin conversion.…”
Section: Challenges and Prospectsmentioning
confidence: 99%